A low power VLSI implementation of distortion correction in image processing ASIC. (2018) - Mohankumar, M.; Gopalakrishnan, V.; Yasotha, S.
Digital video surveillance has emerged to become widely employed in public, medical, private locations, military bases, and so on. Conventional cameras can have coverage of only a small area, resulting in 'blind spots'. They are capable of monitoring about 180° or 360° and therefore they take the place of numerous cameras. This technical work explains about a novel camera system, which employs normal cameras for achieving a broad field of view along with selective focus of interest. This research discusses about a novel non-linear technique for the removal of Barrel distortion in camera images. In order to reduce the complexity, 1-D real chaotic polynomial map is used for approximation. In this proposed work, by using 0.18 μm technology the design can achieve the frequency of 218 MHz having 1490 logic elements. This technique decreases the cost incurred in hardware and the memory usage requirements in comparison with the earlier techniques.